2014
DOI: 10.1007/s12013-014-0376-8
|View full text |Cite
|
Sign up to set email alerts
|

Acrolein-Induced Oxidative Stress and Cell Death Exhibiting Features of Apoptosis in the Yeast Saccharomyces cerevisiae Deficient in SOD1

Abstract: The yeast Saccharomyces cerevisiae is a useful eukaryotic model to study the toxicity of acrolein, an important environmental toxin and endogenous product of lipid peroxidation. The study was aimed at elucidation of the cytotoxic effect of acrolein on the yeast deficient in SOD1, Cu, Zn-superoxide dismutase which is hypersensitive to aldehydes. Acrolein generated within the cell from its precursor allyl alcohol caused growth arrest and cell death of the yeast cells. The growth inhibition involved an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…A strain that was deleted for gene Afu1g09190 (AFUB_008610) was highly sensitive to AA ( Fig 1A and 1B ) but presented no growth defects in non-stress conditions ( S1A and S1B Fig ) nor in the presence of 2-deoxyglucose (2DG), an additional indicator for defects in CCR[ 15 ] ( S1C Fig ). AA is converted by alcohol dehydrogenase (ADH) to acrolein, a highly toxic compound shown to also induce oxidative stress within the cell[ 16 , 17 ]. To investigate any ADH regulatory or activity defects, enzyme activity was measured in the presence of ethanol and ethanol and glucose, with glucose causing the CCR-mediated transcriptional repression of ADH-encoding genes[ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…A strain that was deleted for gene Afu1g09190 (AFUB_008610) was highly sensitive to AA ( Fig 1A and 1B ) but presented no growth defects in non-stress conditions ( S1A and S1B Fig ) nor in the presence of 2-deoxyglucose (2DG), an additional indicator for defects in CCR[ 15 ] ( S1C Fig ). AA is converted by alcohol dehydrogenase (ADH) to acrolein, a highly toxic compound shown to also induce oxidative stress within the cell[ 16 , 17 ]. To investigate any ADH regulatory or activity defects, enzyme activity was measured in the presence of ethanol and ethanol and glucose, with glucose causing the CCR-mediated transcriptional repression of ADH-encoding genes[ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is sensitive to a variety of stress agents due to escalated oxidative stress. Moreover, it also plays a key role in the apoptotic process [ 21 ]. Yca1 mediates the apoptotic process, and encodes a yeast protein with structural homology and similar function to mammalian caspases [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that acrolein, one of the metabolites of CP, is one of the main responsible for the increased production of reactive oxygen species (RS) and lipid peroxidation, which is one of the possible mechanisms responsible for its toxicity [ 5 ]. Oxidative stress is a key factor in the etiology of male infertility, since increased testicular oxidative stress can cause changes in the dynamics of testicular microvascular blood flow and endocrine signaling leading to an increase in germ cell apoptosis and subsequent hypospermatogenesis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%